The Effectiveness of Using Electronic Stick Figures for Teaching Writing Recount Text at Junor High School (RETAIN, 2014)
The Effectiveness of Using Electronic Stick Figures for Teaching Writing Recount Text at Junor High School Fatmah Mahardini English Department, Languages and Arts Faculty, State University of Surabaya fatmah_mahardini@yahoo.com Prof. Dr. Hj. Lies Amin Lestari, M.A., M.Pd English Department, Languages and Arts Faculty, State University of Surabaya lies.aminlestari@yahoo.com Abstrak Menulis dianggap sebagai keterampilan yang paling sulit diantara keterampilan berbahasa lainnya (membaca, berbicara, dan mendengarkan). Sehingga para guru perlu menemukan berbagai cara kreatif untuk pengajaran writing (menulis) daripada hanya meminta siswa menulis tanpa memikirkan bagaimana memberi kemudahan kepada siswa dalam belajar menulis. Karena alasan tersebut, media dibutuhkan dan seharusnya digunakan untuk membantu siswa dalam menguasai kemampuan menulis. Selain itu, penggunaan multimedia dalam proses belajar mengajar dapat membuat materi pembelajaran lebih mudah diingat dan dimengerti. Teori yang mendasari penggunaan multimedia adalah Dual-coding yang dibuktikan oleh Paivio (1986). Olehkarena itu, electronic stick figures dalam bentuk multimedia dipercaya sangat sesuai untuk pengajaran menulis teks recount. Penelitian ini menggunakan desain penelitian eksperimental dengan sampel penelitian yakni grup eksperimen dan grup kontrol yang bertujuan untuk mengetahui efektivitas penggunaan electronic stick figures untuk pengajaran menulis teks recount pada siswa kelas delapan di SMP Negeri 1 Ngoro. Sehingga penelitian ini dilaksanakan untuk mencari perbedaan nilai writing yang signifikan antara grup yang belajar writing menggunakan electronic stick figures dan group yang hanya menggunakan buku dan papan tulis. Nilai-nilai post-test dari kedua grup dibandingkan dengan menggunakan perhitungan t-test. Hasil dari perhitungan tersebut menunjukkan bahwa experimental group yang belajar menulis menggunakan electronic stick figures menunjukkan peningkatan nilai yang signifikan dibandingkan dengan siswa di control grup dengan nilai t 6.067 dan nilai p .0001(df= 88, perbedaan nilai rata-rata9.95). Hasil tersebut menunjukkan bahwa penggunaan electronic stick figures efektif untuk meningkatkan kemampuan siswa dalam menulis teks recount. Kata Kunci: pengajaran writing, electronic stick figures, recount Abstract Writing English is considered as the most difficult skill among the other language skills (reading, speaking and listening). Therefore, it is important for the English teachers to find some creative ways to teach writing instead of only directing student to write without thinking how to facilitate them. Because of that reason, appropriate media is needed and should be used to help students master writing. Moreover, the use of multimedia in teaching and learning process is able to make the lesson become memorable and understandable (Mayer and Simes, 1994). The theory which underlies the use of multimedia is Dual –coding which was proven by Paivio (1986). Therefore, Electronic stick figures in the form of multimedia are believed considerably suitable for teaching writing recount text. Using experimental research design with experimental and control group as the sample, this study was aimed to find out the effectiveness of using electronic stick figures for teaching writing recount text at eighth graders of SMP Negeri 1 Ngoro. Thus, this study was conducted to find the significant difference in term of students’ writing scores between students who are taught by using electronic stick figures and those who are taught by using only book and whiteboard. Using t-test calculation, the scores of post-test of the two groups were compared. The result showed that by using electronic stick figures students in the experimental group scored significantly higher than students in the control group, with the t value of 6.067 and p value of .0001 (df = 88, mean difference 9.95). It shows that the use of electronic stick figures is effective to improve students’ ability in writing recount text. Keywords: Teaching Writing, electronic stick figures, recount INTRODUCTION Students in Junior High School are aimed to be able to communicate both oral and written in functional literacy level (Depdiknas, 2006). In Functional literacy level, students are directed to be able to use English in their daily life for the purpose of transactional communication, such as read manual, understand the meaning of signs, and create functional texts or simple essay. To gain this aim, Junior High school students are taught four English language skills (listening, speaking, reading and writing) equally. As stated by curriculum maker 2006 ,the scope of English lesson in junior high school includes a) the ability to understand and/or create oral and or written texts which will be presented by the combination of listening, speaking, reading, and writing to reach functional literacy level, b) the ability to understand and create short functional texts, monologues and essays in the form of procedure, descriptive, recount, narrative, and report text, c) supportive competence, such as : linguistic, socio-cultural, strategic, discourse competence. Furthermore, recount text is included in the scope of English lesson for Junior High School. The standard competence of writing recount text appears in eight grade of junior high school. It is taught in both odd and even semester. Based on the 2006 curriculum, recount text is taught to eighth and ninth graders in Junior High School. It seems that recount is required to be taught since this level because it has many functions in daily life such as in letter, conversation, and etc. Students often tell their experience in form of recount, but they do not realize that it is in form of recount. Recount is usually compared to narrative. Both look similar, but actually they are not the same. Both of them tell about past event. Narrative tells readers about problematic event which is usually fiction. In contrast, recount does not come to a serious crisis complication and it is usually based on fact. Furthermore, Anderson and Anderson (2003: 24) conclude that a recount text is a piece of text that retells past event, usually in the order in which they occurred, and has purpose to provide the audience with the description of what happened and when it happened. Moreover, Derewianka (1990) states the focus of recount is on a sequence of events, all of which related to a particular occasion. Focusing on the sequence of event may differentiate recount to narrative which focus on a serious crisis of complication and its resolution, besides fiction form. Thus, recount must be taught as clear as possible in order to make students able to write recount in an appropriate text form. However, most of students consider writing as the most difficult skill among the other. As stated by Richard (1997: 100), mastering writing is difficult and needs lengthy process because of anxiety and frustration for many learners. They may reluctant to write because they are de-motivated during the lesson. Furthermore, students are usually confused when they are going to start writing (Emilia, 2008). It seems that they have nothing in their mind about what they are going to write. Sometimes they also have difficulties to express their ideas and have limited vocabularies in producing the text both oral and written. For those reasons, teacher must be aware about the difficulties which are faced by students when they learn writing. As a result, the teacher should take into consideration on some principles to teach writing. Nunan (2003:92) suggests some principles in teaching writing that purposes to make efficient of teaching. These principles can be adapted to the many different learning situations. Firstly, the teachers should understand the students’ reason for writing before going to writing class. In other words, teachers try to expose the students to the usefulness of the activity. It is because students mostly feel dissatisfaction when their goal to write is not suitable with the teachers’. Hence, the teachers should be careful in making writing instruction that match students’ goal. Secondly, the teachers should encourage them to make beneficial effort as much as possible and provide many opportunities for students to write. Because writing is a skill, students need more practices to write. Thirdly, make feedback helpful and meaningful. Students need feedback on their writing although it doesn’t always have intended effect. In other words, teacher may be a motivator, resource, and feedback provider (Harmer, 2001: 216). Teachers sometimes find the difficulties too in the way they explain students about how to write recount text appropriately. This situation usually appears when students seem de-motivated during the lesson. Students are not able to enjoy the lesson because learning writing is such a boring moment. Consequently, students cannot grab the point from teacher’s explanation. From the previous explanation, both teacher and students face difficulty in teaching and learning process. Therefore, teachers should try to find an appropriate and interesting way stimulate students’ excitement in writing activity. There are many possible ways and facilities to support teaching and learning English i.e., exploiting available facilities around us, teachers are aimed to be able to use them efficiently to deliver any information to their students. Furthermore, Brown (2001) and Ur in harmer (2002) called adolescents as teens or young adults who are ranged between 12 and 18 year- old learners which still consider varieties of sensory input as essential factor to assist them in understanding things. In other words, adolescents need alternative material and media in learning language. Adolescents are over all the best learners (Ur, 2000). It is the best time for them to develop their intellectual maturation so teacher should apply creative teaching and facilitate them with suitable media. They also need guidance from the teacher to get maximum result. Thus, material and media used by students should be selected carefully. Nowadays, there are many kinds of media or tools that we can use to deliver information to the students. Anything that can be used to help teacher express or convey what is going to explain to students is called teaching media, also called teaching aids Martin and Brings, 1986). Since technology is rapidly developed, computer becomes a novelty and common thing in educational field. It shifts people’s view to the way of teaching (Sudjana and Rivai, 2007:110). Many educators believe that technology as supporting media in language teaching can overcome the weaknesses of traditional media which is used long before the trend of technology. In the past, teachers taught their students by using traditional media such as blackboard, books, papers, cards, etc. While, nowadays there are many kinds of teaching media which provide certain features for each purpose which are made by computer systems. Furthermore, Abdelraheem & Al-Rabane (2005) explain that technology has a big potential to be encouraged as a tool that can overcome the traditional setting of the classroom which is isolated (Braune,1997) supply access to rich resources (Becker &Ravitz, 1999) and increase overall productivity (Saye, 1998). Thus, it is clear that technology use can create such an easier way of language learning. According to Lesman et al (2009), nowadays, the use of new media is increasing rapidly such as video, educational television, on-line web, blog, and computer games. Since computer becomes a common thing, many kinds of media are created in various forms such as visual aids, audio aids, audiovisual aids, and multimedia. Multimedia is one type of media that can be used to express/ convey what is going to tell to student, whether software or manual. It provides several kinds of teaching aids. It does not only provide one kind of media, such as audio only, but it can provide more than one kind of media. As technology development has touch every part of our life and as education is part of our world, it is interesting to make use of innovative tools and bring it inside classroom. There are a lot of advantages in using computer and multimedia for teaching language in the classroom. We often find a teacher teach a large number of students in the class. Teacher can apply the media which can be shown in a large screen by using computer and LCD projector so it can grab students’ attention. It can also minimize the time consuming compared to the drawing on the blackboard which need time to draw on the blackboard. By the unique features of multimedia, students are interested to learn. Moreover, Marentette and Uhrick (2008) in their article say that the use of multimedia promotes meaningful learning that can be transferred or generalized to other situations. They add that learning is constructive, and information learned is remembered at a deeper level. Besides, multimedia can also improve the academic engagement of students so students can take a part and experience themselves by operating it. MCALL or multimedia courseware is a set of software programmed to help users learn something. The theory which underlies and supports the use of Multimedia courseware in language learning is Dual Coding Theory. Based on dual coding theory stated by Paivio (1986:53), humans have separated information channels, verbal and visual. Their systems are interconnected but each can work independently. He describes that when dual coded, information will be easier to retain and retrieve because the availability of two mental representation instead of one. Therefore students who are taught using multimedia can grab the information easily. Paivio (1991:5) adds that "The common effective process was indeed imagery, which was generated to words, and reactivated by a concrete stimulus image during recall so that the response word could be retrieved from the image." According to Paivio, image has significant effect in helping people imagine something to be delivered in writing. The memory emphasis evolved into broader applications of imagery aimed at creating sentences to express the idea. Electronic stick figure comes from the word electronic and stick figure. The word electronic means something done by computer system and stick figure means a simple picture of a person in which the head is drawn as a circle and the body, arms and legs are drawn as lines (Cambridge, 2008). Stick figures is selected for teaching writing recount to eight graders because it looks so simple but vivid than words and much easier to recall as stated by Richards and Gibson’s in Wijanarko (2006). Stick man or stick figure describing person are easily made by drawing a circle and lines. Not only person’s figure but also figure of building, animal, and fruits can be drawn as stick figures. Stick figures are commonly used in the form of visual media. It is usually drawn conventionally on a paper or blackboard. Before lesson, teacher drew the pictures by using chalks colourfully and wrote the keywords to show the vocabulary. Consequently, teacher should erase the figures after lesson and create again and again in each meeting. While electronic stick figures can be reused in any time. Teacher only needs a laptop to operate this media and LCD projector to display the stick figures to the students. Students can also copy the software from the teacher. Then operate the media by themselves. Hence, the teaching and learning process can be more effective. Electronic stick figures is a teaching aid which has several features containing pictures (in form of stick figures) and words in digital form, not printed form. It can be served through application that created using Macromedia flash player or Microsoft Power Point. The Microsoft office PowerPoint or Macromedia flash player provides many features which can create media such as pictures, words, sounds, or the combination of them. The result file can be shown as PowerPoint Presentation or it can be converted into PowerPoint Show so it is easy to show when it is needed. Electronic stick figures contains menu page which provides some buttons. They are study pages which contain some explanation related to recount text including the language features, figures which contain series pictures for practice writing, and exercise relating to language features in recount text, and game & exercise which provide some exercises related to recount. Hopefully the learning process can run more joyful and using Electronic Stick Figure helps the students to dig up their ideas and construct the text-type more easily both in-groups and individually. Based on the facts above, in this study, the researcher wants to know whether the use of electronic stick figures is effective to teach recount text to eight graders of junior high school or not. METHODOLOGY A two-group experimental research with a quantitative approach was conducted in this study. There were two groups, experimental and control group, which were assigned randomly. Pre-tests and post-test were given to both groups, while the use of electronic stick figures was used in experimental group only. The control group was taught conventionally by using only book and whiteboard. Then, the scores of both groups were compared to find out the significant difference between experimental and control group. This study was conducted in SMP Negeri 1 Ngoro. This school was chosen because it is fully equipped by at least laptops, LCD projectors, and music stereo. However, it was found in preliminary study that the teacher did not use the facilities maximally. Several teachers had used the Multimedia projector in teaching process, but it was considered uninteresting for several students. Thus, it can create the boredom for students. The population in this research was all eighth graders in junior high school. Then, the sample was got from the cluster random sampling where every member of the class in the school had an equal probability of being assigned to any of the groups. Junior High School I Ngoro had eight classes where each class consisted of 23 students. However, an experimental research needs at least 30 students to be the sample of each experimental or control group (Porte, 2002). For that reason, the researcher took two classes to be assigned as experimental group and two other classes as the control group. Thus, the number of students in each group, 46 students, was appropriate. In this study, a cluster sampling was chosen to draw the sample of the study. The groups were assigned based on the students’ original classes; from VIII A to VIII H, since this process helped the researcher and the teacher conduct the study in regard to the effectiveness and the efficiency. Then, a process of random assignment, a process in an experimental study in which the samples of the study to act as control or experimental group are assigned, by doing a lottery. Finally, without purpose class VIII A, VIII B, VIII C, and VIII D were chosen as the sample. By using random assignment, VIII A and VIII C were chosen as control group while VIII B and VIII D were the experimental group. The data in this study were the students’ scores. Therefore, the instrument in this study was test. In this study, the type of the test was subjective test in making English composition especially in writing recount text. The try out was administered before the test was conducted to know the reliability of the test. To measure the reliability of the subjective test, such as the writing test in this study, the inter-rater reliability was used to measure the consistency between raters. The scores were compared to determine the consistency of the raters’ estimates. Heaton (1975: 36) points out that the test will be reliable if the test will be judged by two or more raters. According to Heaton (1975:36) that scoring rubric was included in analytic method. Analytic method marked the writing product separately on its component depended on marking scheme which had been carefully drawn up. The researcher and the English teachers used the ESL composition profile to score them. Ince the test is in the form of subjective test, correlation Pearson product-moment formula to measure the reliability of the test (Bartz, 1976:193). The result was then adjusted to the table below. Table 1: The Criteria of the Reliability of the Test with the Criteria According to Bartz (1976) The Criteria The Description Very High r .80 or above Strong r .60 to .80 Moderate r .40 to .60 Low r .20 to .40 Very Low r .20 or less From the table above, it can be seen that the r coefficient correlation between X (Rater 1) and Y (Rater 2) is 0.839. Based on the criteria of reliability in table 3.4.2, it is very high reliability. In conclusion, the test is reliable, while the content validity of the instrument was measured by relating the content of the instrument to the Standar Isi in Indonesian curriculum. It is written in standard isi in 2006 curriculum. After measuring the test, Pre test and post-test was conducted. A pre-test was used to know the students’ writing ability before the treatment while a post test was used to know the improvement of the students’ writing ability after the treatment. In other words, the pre-test and post-test were conducted to measure whether there would be significant change toward the students score in writing recount text. The time allocation for pre-test and post-test was about 90 minutes. In both pre-test and post-test, all students (both experimental group and control group) got the same worksheet. A quantitative data analysis was conducted in this study. The calculation of students scores in pre-test and post-test was intended to find out the significant difference between the experimental and the control groups which got different treatment. The result of the calculation of t-test is used to find out whether there is any significant difference between two means. There is a significant difference if the t value > t table, but if the t value < t table so there is no significant difference. RESULTS This study is conducted to investigate the significant difference between students who are taught writing recount text by using electronic stick figure and the students who are taught by using only book and whiteboard. Then, it was found that electronic stick figures are effective for teaching writing recount text in junior high school.the effect of using electronic stick to improve students’ achievement in writing recount text was investigated through comparing the mean scores of the pre-test and post-test between the experimental and control group. The significant difference of Pre-test scores of experimental and control groups is presented in the following table: Table 2: Scores of Pretest and Posttest for Experimental and Control Group Test Group df Mean tvalue t.0001 Significant Pre-test score experimental 88 60.31 -3.99 4.053 Not Significant Control 88 67.33 Post-test score experimental 88 80.24 6.067 4.053 Significant Control 88 70.29 Based on the calculation of the scores it was found that the mean of experimental group was 60.31 and Control group was 67.33 to see whether the difference of those scores are significant or not, the researcher calculated t-test. From the table 4.1 above, it can be seen that The tvalue of pre-test scores of experimental and control groups with level significance .0001 and 88 degree of freedom was -3.99 and the ttable was 4.503 ttable was higher than tvalue it means there is no significant difference between two groups. The second step was computing the post-test scores of experimental and control groups and calculated the mean of those groups (see appendix 5). From the calculation, the mean of experimental group was 80.24 and control group was 70.29. The tvalue of posttest scores of experimental and control groups with level significance .0001 and 88 degree of freedom was 6.067 and the ttable was 2.647. Table 2 shows that the tvalue was higher than ttable. It means that there is significant difference between two groups. Thirdly, the researcher compared significant difference between Pre-test and Post-test scores of Experimental Group. The tvalue of pre-test and Post-test scores of experimental with level significance .0001 and 44 degree of freedom was while the ttable was 4.320. ttable was much lower than tvalue it means there is significant difference between pre-test and post-test scores of Experimental group. The table is presented below: Table 3:The Significance of the Difference in the Pre-test and Post-test Scores of Experimental and Control Group Group t value t table df Experimental 19.93 6.52 0.98 20.337 4.320 44 Control 2.96 5.55 0.84 3.52 44 The last calculation is significant difference of pre-test and Post-test scores of control group. The tvalue of pre-test and Post-test scores of control with level significance .0001 and 44 degree of freedom was and the ttable was 4.320. ttable was higher than tvalue it means there is no significant difference between pre-test and post-test scores of Control group. The results above show that there is significant difference between students who were taught writing recount text using electronic stick figures and those who were taught by using only textbook and whiteboard. The results of Pre-test and Post-test prove that the experimental group’s score developed after getting treatments. The development of their means is illustrated through the figure below: Figure 1: The Comparison Means of Experimental and Control Group in Total Score of Students’ Writing Considering the results of pre-test and post-test it could be seen that the ability of experimental group now is getting higher than it was before and also higher than control group. It seems that the treatments given to experimental group were successfully done. Then, hypothesis “There is significant difference in the term of score between students who are taught writing recount text by using electronic stick figures and those who are taught by using only textbook and whiteboard was accepted. In conclusion, the use of electronic stick figures could improve student’s writing skill, especially in writing recount texts. DISCUSSION From the analyzed data, the researcher concludes that there is no significant difference between the students’ scores in pre test. They show the similar result. Their t values are lower than t table. It means that they have equal ability in writing recount text before experimental group was given treatments. Otherwise, the experimental group shows the higher score than control group in post-test. The reasons why the experimental group got much higher score in post-test are because of the effect of the treatments. During the treatments, students looked motivated in the classroom. It was shown when they tried to take a role in the learning activity. Students participated to answer the teacher’s question and give more response in the section of giving feedback. The qualities of responses which students show in giving feedback ensure the researcher that they had been understand the learning material better. Consequently, the writing product was more valuable. They had been able to develop their ideas in each paragraph, use the effective vocabulary, and appropriate grammar (see appendix 12). Based on table 4.3, it looks obvious that electronic stick figures are effective in teaching writing recount for eighth graders. It is needed to analyze further about how the treatment might work to the students. In this research, the researcher gave different method in giving treatments to both groups. The experimental group were given treatments for three times by using electronic stick figure as teaching aid. On the other hand, the researcher did not give special treatment to control group. The teacher did not use electronic stick figure as teaching aid as it was used by experimental group. During the teaching learning process, the researcher only explained about recount text as usual. Researcher explained the lesson by using only textbook and whiteboard. Consequently, it makes the students get bored and lost their interest to learn English. Even though control group also worked in group during the treatment, they looked unmotivated. It seemed difficult for them to explore their ideas. On the contrary, the experimental group were so enthusiastic and pay more attention when the teacher explains the material and when the teacher asked them to write recount text, they did it vigorously. They did the assignment actively, operated the media by themselves and took a role in the group to share their ideas. Even though they had some difficulties in grammar, vocabulary, and organization in writing recount, they had solutions to overcome these difficulties by finding the keywords on the picture. Besides, the situational of stick figures make students easier to identify the generic structure and language feature of recount text. Meanwhile, the chart of stick figure with their relevant keyword and sentences make the genre more familiar and the class gets a common basic understanding about it. Besides, the situational stick figure performed part by part gives students better understanding about the chronological events, the generic structure and language feature. Thus, the experimental group enjoy the treatments and were able to write recount text effectively. Then, experimental group showed the higher mean scores than control group in the post-test with the significance difference in the .0001 level for 88 degree of freedom. For the detail of the result, It can be seen in table 4.2. The differences of the writing result were in the area of using relevant word in constructing sentences and developing the ideas in each paragraph (see the appendix 12). In the post test, students are able to construct the relevant words into sentences. They could also use the appropriate tenses in writing recount text. The number of errors in post test in less then in the pre test. The significant difference between the experimental and control group was caused by the different method above. The use of electronic stick figures influences students’ ability in writing recount text. They were helped by the media to dig up their ideas to be conveyed in written form. As stated by Brown (2001:92), teen still needs variety of sensory input which is important to develop their critical thinking. Sensory input can be in the form of verbal (speech or writing) or non verbal (a symbolic function with respect to nonverbal objects or pictures, events, and behaviours). Electronic stick figures provide both verbal and non verbal to stimulate students critical thinking. The researcher uses Pavio’s theory to apply this kind of media in teaching and learning process named Dual Coding theory. This theory describes that cognition consists of representational systems called verbal and nonverbal systems. According to this theory, words and sentences are processed and encoded in the verbal system, while images are processed and encoded in the nonverbal system (Paivio, 1971, 1986, 1991). These coding systems are separated but interconnected so that they can operate independently, in parallel, or through their interconnections. The linguistic, or verbal, code dominates in some tasks, the nonverbal code dominates in others, and both systems are frequently used together so the information can be more memorable and understandable. Because of this theory, electronic stick figures works well in experimental group. Students are able to explore their ideas by decoding the words and pictures presented in the electronic stick figures. Another factor was related to motivation. It was clear that the students were enthusiastic and motivated to write a recount text by engaging themselves to the learning writing process. Harmer (2002: 40) stated that motivation is crucial factor in successful learning. By having a good motivation, students could learn language better and faster than students who have low motivation in learning language. Compared to previous study which was conducted by Wijanarko (2006), the writing result between students who are taught by using electronic stick figures and those who are taught by using stick figures drawn on the blackboard shows insignificant difference. Both studies show the positive effect to students who learn writing recount whether using electronic stick figures or stick figures with blackboard drawing. The t-value shows -0.097 where its value is lower than t- table 4.053 (see appendix 14). Wijanarko (2006) wanted to find out how Stick Figure improves students’ ability in writing Recount of class VIII-A SMPN 1 Lumajang. He needed twelve meeting to conduct his classroom action research. He conducted writing test four times in the 6th, 8th, 10th, and 12th. Learning materials which he gave were different for each meeting. Then, he concluded that stick figures are able to arouses the students’ interest and attracts their attention, create an atmosphere in which students learned English naturally, bring the classroom into a live language situation which involved both language patterns already learned, represent the coherence and unity of the entire text and guides the students to construct the text based on the generic structure and the language feature of the text. The result of the study conducted by Wijanarko (2006) was also influenced by the number of meeting he used to teach his students. In 1st – 5th meeting, students in SMPN 1 Lumajang were introduced about stick figures and got explanation about recount. They have five days to know about recount text and how they understand the situational stick figures so they understand the material better. Otherwise, this study needed only two meeting to explain about the media and the lesson. Then, total meeting which was used for classroom action research conducted by Wijanarko (2006) was twelve meeting while this study, using electronic stick figures, just needed six meeting. The more meeting students get for learning the better result they get. Using electronic stick figures may show the better result in term of writing score if this media was applied in appropriate time. However, multimedia has an important role in this study. Compared to the stick figures drawn on the blackboard, electronic stick figures are created in a form of multimedia which has several advantages. Electronic stick figures were created using computer software, Microsoft Power Point 2007, which can be reused by the teacher or the students themselves. Consequently, teacher does not need to draw figures in each meeting. As teacher does not need to draw figures on the blackboard, teaching and learning process can run faster by operating electronic stick figures. CONCLUSIONS AND SUGGESTIONS Conclusions who were taught writing recount text using electronic stick figures, achieved higher scores at post-test than control group who were taught writing recount text by using only textbook and whiteboard. It is proven by the result of Post-test of experimental and control groups. The mean of experimental group is 80.24while control group is 70.29. Moreover, from the distribution of t test it was found that the result of tvalue of Post-test scores of experimental and control groups with 88 degrees of freedom is 6.067while the t.0001 is 4.503 it can be seen that tvalue is higher than ttable. The hypothesis, which says that there is significant difference in the term of score between students who are taught writing recount text by using electronic stick figures and those who are taught by using only textbook and whiteboard. The null hypothesis then is rejected. It can be said that using electronic stick figures in teaching writing recount text had significant influence to improve the students’ writing ability. In addition, the result of the study also supports the Dual Coding Theory which was established by Allan Paivio (1989). According to this theory, words and sentences are processed and encoded in the verbal system, while images are processed and encoded in the nonverbal system. For this reason, the combination between visual codes and verbal codes are more memorable and understandable. Thus, electronic stick figures in the form of multimedia which applies dual coding theory is effective for teaching writing recount text at Junior High School who still needs a sensory input to stimulate their imagination in writing activity. Suggestions Considering the result of this study which found that there is significant difference between students who were taught writing recount text using electronic stick figures and those who were taught by using only textbook and whiteboard, the researcher suggests some important things to those who are related to the result of this study, they are the English teacher, Multimedia developer, and the next researchers as well. To the English teacher, it is necessary to explore the use of electronic sick figures in teaching writing or combine the media with other teaching techniques to stimulate students to write text easily. It is also intended to avoid the monotonous activity in the class. The teacher should be aware of development of technology; even they should be able to use technology for teaching. Then, to the multimedia developers, the researcher hopes that they can be more creative in creating Multimedia Courseware to assist language learners in learning English. Electronic Stick figures are designed by using Microsoft Power Point 2003- 2010, they can also be designed by using Macromedia Flash Player or other similar applications. The last suggestion is given to the next researchers who might be interested in investigating the similar study. Since this study focused on the effectiveness of using electronic stick figures in writing recount text at Junior High School Students, hopefully the next researchers can develop the similar media to other skills or subjects for the next studies. REFERENCES Anderson, M., & Anderson, K. (1998). Text Types in English 3. Australia. Macmillan. Brown, H. Douglass. 2000. Principles of language learning and teaching. New York: Addison Wesley Longman, Inc. Brown, H. Douglas. (2001). Teaching by Principles: An Interactive Approach to Language Pedagogy, 2nd ed. New York: Addison Wesley Longman, Inc. Depdiknas. (2006). Standar Kompetensi Mata Pelajaran Bahasa Inggris. Jakarta: Departemen Pendidikan Nasional Dolati, R. & Richard, C. (2010). Harnessing the Use of Visual Learning Aids in the English Language Classroom. Arab World English Journal, Vol. 2, 3-17. Emilia, R.T. (2008). Increasing Students’ Writing Skill Using Picture Strip Story (A Classroom Action Research at the Fist Grade of MTS Ma’Hadul Muta’alimin Katerbang Ngawi). Muhammadiah University of Surakarta. Harmer, J. (2001). The Practice of English Language Teaching. Edinburg: Pearson Education Limited. Nunan, David. (2003). Practical English language teaching. Singapore: The Mc. Graw-Hill Companies. Nunan, David. (1999). Second Language Teaching & Learning. Boston: Houghton Mifflin company Marentette, L. & Uhrick, A. (2010). Reaching Learners: Immersive Education through interractive Multimedia. North Caroline Paivio, A. (1971). Imagery and verbal processes. New York: Holt, Rinehart,and Winston. Paivio, A. (1986). Mental representations: A dual coding approach. New York: Oxford University Press. Porte, G.K., 2002. Appraising Research in Second Language Learning a Practical Approach to Critical Analysis of Quantitative Research. University of Granada. Amsterdam/Philadelphi, John Benjamins Publishing Company. Ur, Penny. (2000). A Course in Language Teaching: Practice and Theory. Canbridge: Cambridge University Press.